Evaluation of SiC Schottky diodes using pressure contacts - Ortiz Gonzalez, J.; Alatise, O.; Aliyu, Attahir Murtala; Rajaguru, Pushparajah; Castellazzi, Alberto; Ran, L.; Mawby, P.; Bailey, Christopher (Institute of Electrical and Electronics Engineers, 2017)
The thermomechanical reliability of SiC power devices and modules is increasingly becoming of interest especially for high power applications where power cycling performance is critical. Press-pack assemblies are a trusted and reliable packaging solution that has traditionally been used for high power thyristorbased applications in FACTS/HVDC, although press-pack IGBTs have become commercially available more recently. These press-pack IGBTs require anti-parallel PiN diodes for enabling reverse conduction capability. In these high power applications, paralleling chips for high current conduction capability is a requirement, hence, electrothermal stability during current sharing is critical. SiC Schottky diodes not only exhibit the advantages of wide bandgap technology compared to silicon PiN diodes, but they have significantly lower zero temperature coefficient (ZTC) meaning they are more electrothermally stable. The lower ZTC is due to the unipolar nature of SiC Schottky diodes as opposed to the bipolar nature of PiN diodes. This paper investigates the implementation and reliability of SiC Schottky diodes in press-pack assemblies. The impact of pressure loss on the electrothermal stability of parallel devices is investigated.